Medieval monasticisms forms and experiences of the monastic life in the Latin West - Vanderputten, Steven 1976- (De Gruyter Oldenbourg, 2020)
From the deserts of Egypt to the emergence of the great monastic orders, the story of late antique and medieval monasticism in the West used to be straightforward. But today we see the story as far 'messier' - less linear, less unified, and more historicized. In the first part of this book, the reader is introduced to the astonishing variety of forms and experiences of the monastic life, their continuous transformation, and their embedding in physical, socio-economic, and even personal settings. The second part surveys and discusses the extensive international scholarship on which the first part is built. The third part, a research tool, rounds off the volume with a carefully representative bibliography of literature and primary sources
Keywords: Geschichte Anfänge-1500; Geschichte 500-1500; HISTORY / Medieval; Mönchtum; Europa; Bibliografie; Lehrbuch